An Assessment of Abuse of Children with Disabilities at Japanese Nursery Schools: Reports by Commissioned Pediatricians - Horiguchi, Toshihiro; Takanashi, Kenji; Sato, Shoichi; Sone, Naoki (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: In a preschool setting, childcare is usually provided to children with disabilities or potential features as well. In this study, we hypothesized that parents might have additionally consulted commissioned pediatricians when their children were reportedly abused by schoolteachers as well as following legitimate grievance procedures. Aims: To estimate the prevalence rate of children with disabilities being abused at nursery schools in Japan, the authors asked the help of commissioned pediatricians of nursery schools. Methods: We sent a questionnaire to 1,607 members of the Japanese Society for Well-being of Nursery-schoolers, who are specialists known to be highly sensitive to abuses. Incident reports from the second half of 2012 to the fiscal year 2014 were collected from 361 members who replied. Results: In total, three respondents, including one pediatrician, had received a complaint(s) from parents that their child with disabilities had been abused by a teacher. No details on each case were provided. Conclusion: Thus, the need for another assessment to administrative was indicated.